An investigation of continuous variable transmission application on wind turbine / Eliz Azima Abd Aziz - Abd Aziz, Eliz Azima (2009)
The goal of this research is to investigate the possibility of using a continuous variable transmission (CVT) in a wind turbine application. The propose of simulation is to see whether a CVT can be used to let the rotor speed follow the wind speed profile and thus keeping the tip speed ratio, X constant. Working principle of continuously variable transmission (CVT) applying in wind power system is analyzed. Mathematic model of CVT in wind power is established. The relation between wind energy utilization coefficient (Cp), power and wind speed are studied. The CVT, wind turbine rotational speed, wind energy utilization coefficient, generator's rotational speed, wind turbine power and generator power are simulated when wind speed signals are random changed. After which the design and simulation of the system was undertaken using Matlab/Simulink. Simulation results show that wind power applying CVT makes wind turbine operate at an optimal blade tip speed ratio, obtain an optimal wind energy utilizing coefficient, take full advantage of wind energy and be superior to fixed pitch wind power. Generator outputs constant frequency voltage and smoothly variable powers without applying other electric power and electronic equipments.